Analysis of Comorbidities and Smoking History with The Incidence of Pulmonary Tuberculosis at Surakarta General Hospital - Warasti, Irlisa Rahma; Wulandari, Windi (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Tuberculosis (TB) is an infectious disease that is the top cause of death worldwide. Indonesia has the second-highest tuberculosis incidence in the world after India. One of the risk factors for tuberculosis that is difficult to avoid is smoking and comorbidities associated with decreased body resistance. Surakarta Central General Hospital has excellent pulmonary disease services. The healthcare facility treated the highest number of registered and treated pulmonary Tuberculosis patients in Surakarta City in 2019-2021. Objective: This study aims to determine whether there is a relationship between comorbidities and smoking history and the incidence of Pulmonary Tuberculosis at the Surakarta Central General Hospital. Methods: This research was conducted at the Surakarta Central General Hospital in March 2022. Sample withdrawal was carried out using nonprobability sampling with a purposive sampling technique. The data sources used in this study include secondary data from medical records confirmed by primary data by interviewing and distributing questionnaires. This study is an observational quantitative study with a case-control research design. The sample of this study amounted to 96 people (48 case groups and 48 control groups). Data analysis using the chi-square test. Results: The results showed that there was an association between comorbidities (p=0.040; OR=3.541; 95%CI=1,160-10,808) and smoking history (p=0.048; OR=3.182; 95%CI=1,113-9,100) with the incidence of pulmonary tuberculosis. Most patients were male, with the highest age range of 45-54, as many as 24 people, and 55-64 years, as many as 24. Most patients did not have a job (24 people) and had an income ≥ UMR (56 people). Patients' highest level of education was primary education (37 people). Conclusion: This study concludes an association between comorbidities and smoking history with the incidence of pulmonary tuberculosis in Surakarta General Hospital.